Photoabsorption and photoionization studies of the amino acid proline in the VUV region - Coutinho, L. H. (2005)
Ionic fragmentation of the sublimated amino acid DL-proline has been studied using time-of-flight mass spectrometry and synchrotron radiation. Total ion yield and mass spectra were recorded in the 13 to 21.6 eV energy range. Partial ion yields have been calculated for the produced fragments and the results analyzed in a comparative way. Mass spectrum of proline previously obtained at 21.21 eV using photons from a discharge lamp (He I), was used as reference in the comparison to the synchrotron radiation based spectra. The loss of the COOH fragment represents the most probable dissociation pathway following the photoionization of DL-proline in the valence region. These are the first results of total and partial ion yields spectra for this molecule in its gas phase in the valence region using time-of-flight spectrometry.